Pelatihan Implementasi Asesmen pada Kurikulum Merdeka bagi Guru SMAN 3 Purwokerto - Didik Rilastiyo Budi; Lalita Melasarianti; Arfin Deri Listiandi; Rindha Widyaningsih; Septi Mariasari; Kusnandar Kusnandar; Panuwun Joko Nurcahyo (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
The implementation of Community Service (PKM) activities aims to provide seminars and training to SMAN 3 Purwokerto teachers regarding the implementation of assessments or evaluations contained in the independent curriculum and will be implemented in the new academic year 2022/2023. The PKM method uses a seminar and training approach. Seminars are conducted by providing knowledge and understanding materials to participants, while training methods are carried out by participants and resource persons conducting direct practice in the implementation of assessments or evaluations contained in the independent school-level curriculum. The number of participants in the activity was 40 teachers from class X-XII who taught various subjects. The response given by the service partners was very good, so that this service activity could be carried out smoothly and participants were actively involved in discussion and question and answer activities. The results obtained from PKM activities are based on the results of the final test of the level of teachers' understanding of the independent curriculum and the implementation of cement or evaluation of the independent curriculum, there are 24 teachers or 60% who have begun to understand about the independent curriculum that will be applied in schools. With the increasing understanding of teachers regarding the implementation of the independent curriculum, it is hoped that the implementation of the independent curriculum can run well in schools. However, various seminars, training and workshop programs need to be continuously improved to strengthen the knowledge and skills of teachers in implementing the independent curriculum, especially at the assessment stage or student learning assessment